Different paths, same destination: divergent action potential responses produce conserved cardiac fight‐or‐flight response in mouse and rabbit hearts. (11th July 2019) - Wang, Lianguo; Morotti, Stefano; Tapa, Srinivas; Francis Stuart, Samantha D.; Jiang, Yanyan; Wang, Zhen; Myles, Rachel C.; Brack, Kieran E.; Ng, G. André; Bers, Donald M.; Grandi, Eleonora; Ripplinger, Crystal M.
Abstract : Key points: Cardiac electrophysiology and Ca 2+ handling change rapidly during the fight‐or‐flight response to meet physiological demands. Despite dramatic differences in cardiac electrophysiology, the cardiac fight‐or‐flight response is highly conserved across species. In this study, we performed physiological sympathetic nerve stimulation (SNS) while optically mapping cardiac action potentials and intracellular Ca 2+ transients in innervated mouse and rabbit hearts. Despite similar heart rate and Ca 2+ handling responses between mouse and rabbit hearts, we found notable species differences in spatio‐temporal repolarization dynamics during SNS. Species‐specific computational models revealed that these electrophysiological differences allowed for enhanced Ca 2+ handling (i.e. enhanced inotropy) in each species, suggesting that electrophysiological responses are fine‐tuned across species to produce optimal cardiac fight‐or‐flight responses. Abstract: Sympathetic activation of the heart results in positive chronotropy and inotropy, which together rapidly increase cardiac output. The precise mechanisms that produce the electrophysiological and Ca 2+ handling changes underlying chronotropic and inotropic responses have been studied in detail in isolated cardiac myocytes. However, few studies have examined the dynamic effects of physiological sympathetic nerve activation on cardiac action potentials (APs) and intracellular Ca 2+ transients (CaTs) in the intact heart. Here, we performed bilateral sympathetic nerve stimulation (SNS) in fully innervated, Langendorff‐perfused rabbit and mouse hearts. Dual optical mapping with voltage‐ and Ca 2+ ‐sensitive dyes allowed for analysis of spatio‐temporal AP and CaT dynamics. The rabbit heart responded to SNS with a monotonic increase in heart rate (HR), monotonic decreases in AP and CaT duration (APD, CaTD), and a monotonic increase in CaT amplitude. The mouse heart had similar HR and CaT responses; however, a pronounced biphasic APD response occurred, with initial prolongation (50.9 ± 5.1 ms at t  = 0 s vs . 60.6 ± 4.1 ms at t  = 15 s, P  < 0.05) followed by shortening (46.5 ± 9.1 ms at t  = 60 s, P  = NS vs. t  = 0). We determined the biphasic APD response in mouse was partly due to dynamic changes in HR during SNS and was exacerbated by β‐adrenergic activation. Simulations with species‐specific cardiac models revealed that transient APD prolongation in mouse allowed for greater and more rapid CaT responses, suggesting more rapid increases in contractility; conversely, the rabbit heart requires APD shortening to produce optimal inotropic responses. Thus, while the cardiac fight‐or‐flight response is highly conserved between species, the underlying mechanisms orchestrating these effects differ significantly. Key points: Cardiac electrophysiology and Ca 2+ handling change rapidly during the fight‐or‐flight response to meet physiological demands. Despite dramatic differences in cardiac electrophysiology, the cardiac fight‐or‐flight response is highly conserved across species. In this study, we performed physiological sympathetic nerve stimulation (SNS) while optically mapping cardiac action potentials and intracellular Ca 2+ transients in innervated mouse and rabbit hearts. Despite similar heart rate and Ca 2+ handling responses between mouse and rabbit hearts, we found notable species differences in spatio‐temporal repolarization dynamics during SNS. Species‐specific computational models revealed that these electrophysiological differences allowed for enhanced Ca 2+ handling (i.e. enhanced inotropy) in each species, suggesting that electrophysiological responses are fine‐tuned across species to produce optimal cardiac fight‐or‐flight responses.